Knowledge, Attitude, and Practice of Healthcare Professionals of Pakistan Regarding Consumption of Carbonated Drinks: KAP of Pakistani Healthcare Professionals on Carbonated Drinks - Shahid, Javeriya; Jalal, Mohsina; Shakoor, Asma; Nisar, Zarbakht; Usama, Muhammad; Ashraf, Javariya (Pakistan Journal of Health Sciences, 2026)
Carbonated drinks contain acidic ingredients and high amounts of sugar. Such constituents lead to adverse oral and systemic manifestations, such as caries, dental erosion & hypersensitivity, diarrhea, GERD, respiratory, and bone disorders. Objectives: To determine the awareness, attitude, and practice of healthcare workers regarding carbonated drinks and to gauge their attitude and consumption habits regarding these drinks. Methods: A cross-sectional study was carried out across Pakistan, over eight months from January 2022 to August 2022. There was adequate representation from all provinces, and 1930 MBBS, BDS, and Allied Health Science workers filled out a pre-tested questionnaire. These professionals had different designations in government and private setups. A non-probability convenience sampling was done. Frequency and percentages depicted the data. One-way ANOVA was performed to compare composite knowledge and attitude scores, while Chi-square tests with Cramer’s V were used for practice variables. Results: 97.5% of the healthcare workers knew about carbonated drinks, but only 85.1% were aware of their composition, whereas 93.1% knew about their side effects. 34.4% consumed carbonated drinks with meals. 87.2% believed that carbonated drinks have harmed teeth, and 60.2% experienced changes in the oral environment. Conclusions: Despite an abundance of knowledge regarding the composition and harmful effects of carbonated beverages, their consumption was high among the targeted population.